Adding Coffee to Reduce the Typical Flavor of Fish in Hawaiian Ladyfish Skin Gelatin Marshmallows - Ulil Azizah; Sakinah Haryati; Rifki Prayoga Aditia (JURNAL PERIKANAN DAN KELAUTAN, 2024)
Gelatin is one of the ingredients in making marshmallows. The gelatin on the market comes from cows and pigs, so its halal is still doubtful, and these animals can be infected with diseases that are dangerous for consumers. An alternative source to overcome this problem is gelatin, which comes from the skin of hawaiian ladyfish. The use of hawaiian ladyfish skin gelatin in marshmallows still produces the typical flavor of fish, therefore in this research the addition of coffee was carried out to reduce the typical flavor of fish in marshmallows because coffee has volatile compounds and caffeine which can produce a distinctive aroma and taste in coffee. The aim of this research was to determine the best coffee concentration for reducing the typical flavor of fish in hawaiian ladyfish skin gelatin marshmallows. This research was conducted in July–September 2023. This research used a completely randomized design (CRD) with two replications and one treatment factor, namely coffee concentration (0%, 5%, 10%, 15%). This research consists of three stages, namely making gelatin, brewing coffee, and making marshmallows. The results of this study indicate that 10% coffee concentration is the best treatment for hawaiian ladyfish skin gelatin marshmallows with a water content of 23.68%, ash content of 0.65%, reduced sugar content of 20.19%, and TPC of 2.95 x 10¹ colonies/g. The results of the hedonic test showed that the panelists gave an average rating of